Nonlinear response speedup in bimodal visual-olfactory object identification - Höchenberger, Richard; Busch, Niko A.; Ohla, Kathrin (Frontiers in Psychology, 2015)
Multisensory processes are vital in the perception of our environment. In the evaluation of foodstuff, redundant sensory inputs not only assist the identification of edible and nutritious substances, but also help avoiding the ingestion of possibly hazardous substances. While it is known that the non-chemical senses interact already at early processing levels, it remains unclear whether the visual and olfactory senses exhibit comparable interaction effects. To address this question, we tested whether the perception of congruent bimodal visual-olfactory objects is facilitated compared to unimodal stimulation. We measured response times (RT) and accuracy during speeded object identification. The onset of the visual and olfactory constituents in bimodal trials was physically aligned in the first and perceptually aligned in the second experiment. We tested whether the data favored coactivation or parallel processing consistent with race models. A redundant-signals effect was observed for perceptually aligned redundant stimuli only, i.e. bimodal stimuli were identified faster than either of the unimodal components. Analysis of the RT distributions and accuracy data revealed that these observations could be explained by a race model. More specifically, visual and olfactory channels appeared to be operating in a parallel, positively dependent manner. While these results suggest the absence of early sensory interactions, future studies are needed to substantiate this interpretation.